Assessing the Major Aspects and Implications of Telerehabilitation Services: A Bibliometric Analysis - Osama Khalil Alyacoubi; Maria Ulfa; Arlina Dewi (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
Telerehabilitation has emerged as a promising option for delivering rehabilitation services to individuals with physical impairments, but its effectiveness, efficiency, and economic implications are not yet fully understood. This study explores the relationship between telerehabilitation services and various aspects of healthcare delivery, including treatment, quality, outcome, and delivery of telerehabilitation. The Scopus database (https://www.scopus.com) with the term "Telerehabilitation Services" from 2012 to 2021 was used to gather the most recent evidence for this type of research: qualitative research on telerehabilitation services. Studies reporting on clinical outcomes and delivery of healthcare topics were included in the selected publications. VOSviewer, MAXQDA Analytic Plus, and Nvivo 12 Plus analytical tools assisted data analysis and extraction procedures. The findings indicated that telerehabilitation directly impacts health, with a very strong correlation value of 0.962644. Therapy, Aged, Stroke, Telemedicine, COVID-19, Treatment, Quality, Outcome, and Delivery also showed a strong correlation ranging from 0.851146 to 0.921129. Telerehabilitation services had a significant relationship with technology, physiotherapy, and feasibility, with a correlation ranging from 0.427715 to 0.572538. Challenges include the need for appropriate technology and infrastructure, data privacy and security concerns, and the potential for technology-related errors. Telerehabilitation significantly influenced healthcare delivery, including stroke, COVID-19, treatment, quality, outcome, delivery, technology, physiotherapy, and feasibility. Challenges remain, and further research is needed to evaluate cost-effectiveness in different settings and populations. Technology can enhance patient outcomes with proper planning, training, and support.